Low‐gluten, nontransgenic wheat engineered with CRISPR/Cas9 - Sánchez‐León, Susana; Gil‐Humanes, Javier; Ozuna, Carmen V.; Giménez, María J.; Sousa, Carolina; Voytas, Daniel F.; Barro, Francisco (Plant biotechnology journal, 2018)
Summary Coeliac disease is an autoimmune disorder triggered in genetically predisposed individuals by the ingestion of gluten proteins from wheat, barley and rye. The α‐gliadin gene family of wheat contains four highly stimulatory peptides, of which the 33‐mer is the main immunodominant peptide in patients with coeliac. We designed two sgRNAs to target a conserved region adjacent to the coding sequence for the 33‐mer in the α‐gliadin genes. Twenty‐one mutant lines were generated, all showing strong reduction in α‐gliadins. Up to 35 different genes were mutated in one of the lines of the 45 different genes identified in the wild type, while immunoreactivity was reduced by 85%. Transgene‐free lines were identified, and no off‐target mutations have been detected in any of the potential targets. The low‐gluten, transgene‐free wheat lines described here could be used to produce low‐gluten foodstuff and serve as source material to introgress this trait into elite wheat varieties.